UTILIZING INTERACTIVE TECHNOLOGY AND ARTIFICIAL INTELLIGENCE FOR 21ST-CENTURY TEACHERS - Syaddam Rijali; Rahmy Febriani Ritonga; Riski Ananda Nasution; Anita Adinda (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to describe the utilization of interactive technology and artificial intelligence (AI) to enhance the competencies of 21st-century teachers within the Educational Coordination Office of Pangkatan Sub-District, Labuhanbatu Regency, North Sumatra Province. The research employed a descriptive qualitative method with a field study approach through a six-day workshop. The subjects of this study consisted of 20 elementary school teachers who participated in training sessions on Quizizz, Wordwall, and the use of AI tools such as ChatGPT in the learning process. Data were collected through observation, interviews, pre-test and post-test assessments, as well as documentation, and were analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate a significant improvement in teachers’ understanding and skills in integrating interactive technology and AI into the learning process. The average pre-test score of 70.00% increased to 89.00% in the post-test, indicating a 19.00% improvement in competency. In addition, teachers successfully developed gamification-based learning media using Quizizz and Wordwall, and utilized artificial intelligence to efficiently design teaching materials and evaluation tasks. The workshop activities also fostered teachers’ motivation, creativity, and digital awareness regarding the importance of innovation in 21st-century education.This study affirms that the integration of interactive technology and AI not only enhances teachers’ pedagogical competencies but also contributes to the development of a more adaptive, collaborative, and digitally relevant learning ecosystem aligned with the needs of the modern era.